Consumer redress and non-redress practices - Lansang, Maria Luisa C.
ABSTRACT This study identified consumer responses from defective goods or services received. Specifically, described consumer redress and alternative redress seeking behavior, nature of complaints, level of complaints, compensations and period of resolution of defective goods and services.The respondents of the study were eighty (80) male and female constituents of the University of the Philippines Community selected through purposive sampling aged 18 years old and above. Responses of the respondents were subjected to frequency, percentages and rank. Findings of the study showed that sixty eight (68) percent of the respondents sought redress when encountered with unsatisfying goods or services received. The study revealed that thirty two (32) percent of the respondents hesitated to redress due to the following: Time Consuming, Cost of item is not worth to seek redress and unknowledgeable to whom to redress. The study revealed that if consumers received defective goods and unsatisfactory services, complaints were directed to the following: talking to the manager, writing a letter of complaint and filing complaint to the concerned agency. The findings of the study revealed that the complaints of the respondents were attended through proper compensation such as replacement of the product, repair, or refund in a very short period of time. The results of the study also indicated that highly priced products versus lowly priced products generated a higher incidence of complaints.